PENGARUH PENGALAMAN, INDEPEDENSI, SKEPTISME PROFESIONAL AUDITOR PADA PENDETEKSIAN KECURANGAN - Indira Biksa, Ida Ayu; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
Auditing is a process that aims to give an opinion on the fairness of the financial statements. In addition to giving an opinion on the fairness of the financial statements, the auditor is also responsible for reporting the findings of fraudulent financial statements, if any. This study aimed to examine the effect of experience, independence and professional skepticism towards fraud detection. This study was conducted on seven public accounting firm in Bali. The sample used are 40 auditors. The sample in this research was determined by the method of sampling nonprobability with saturated sampling technique. Data were collected using questionnaires. Data analysis technique used is Multiple Linear Regression Analysis. Based on the analysis found that the auditor's experience a positive effect on fraud detection, auditor independence a positive effect on the detection of fraud and the auditor's professional skepticism positive effect on the detection of fraud.
Keywords: Experience, Independence, Professional Skepticism, Fraud Detection